Gene expression profile of antithrombotic protein c defines new mechanisms modulating inflammation and apoptosis - Joyce, D E; Gelbert, L; Ciaccia, A; DeHoff, B; Grinnell, B W (The Journal of biological chemistry, 2001)
Human protein C is a natural anticoagulant factor, and a recombinant activated form of the molecule (rhAPC) is completing clinical evaluation for treatment of severe sepsis. Because of the pathophysiologic role of endothelial dysfunction in severe inflammatory disease and sepsis, we explored the possibility that rhAPC might directly modulate endothelial function, independent of its anticoagulant activity. Using broad transcriptional profiling, we show that rhAPC directly modulates patterns of endothelial cell gene expression clustering into anti-inflammatory and cell survival pathways. rhAPC directly suppressed expression of p50 and p52 NFkappaB subunits, resulting in a functional decrease in NFkappaB binding at target sites. Further, rhAPC blocked expression of downstream NFkappaB regulated genes following tumor necrosis factor alpha induction, including dose-dependent suppression of cell adhesion expression and functional binding of intracellular adhesion molecule 1, vascular cell adhesion molecule 1, and E-selectin. Further, rhAPC modulated several genes in the endothelial apoptosis pathway, including the Bcl-2 homologue protein and inhibitor of apoptosis protein. These pathway changes resulted in the ability of rhAPC to inhibit the induction of apoptosis by the potent inducer, staurosporine. This new mechanistic understanding of endothelial regulation and the modulation of tumor necrosis factor-induced endothelial dysfunction creates a novel link between coagulation, inflammation, and cell death and provides insight into the molecular basis for the efficacy of APC in systemic inflammation and sepsis.